2010
DOI: 10.1590/s1519-566x2010000400001
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and fitness in egg parasitoids

Abstract: -Several proxies can be used to estimate the fi tness of egg parasitoids: size, longevity, fecundity, mating ability and vagility. All these proxies are positively correlated with the lifetime fi tness gain of an individual. However, the phenotypic plasticity, which is the ability of a genotype to produce distinct phenotypes depending on environmental conditions, may alter the value of these proxies. Host related factors (host species and quality), competition and duration of development will infl uence the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 61 publications
1
35
0
1
Order By: Relevance
“…Phenotypic and other types of variation is also well documented in other genera of Mymaridae, e.g., Segoli & Rosenheim (2015) for metatibia length in one species of Anagrus, and in other families of egg parasitoids, e.g., Boivin (2010) and Abram et al (2016, and references therein) discussed variation in various feature due to host, phenology, etc. Johnson et al (1987) showed that host-related antennal variation occurs in a polyphagous egg parasitoid, Telenomus alsophilae Viereck (Platygastridae, Telenominae).…”
Section: Discussionmentioning
confidence: 85%
“…Phenotypic and other types of variation is also well documented in other genera of Mymaridae, e.g., Segoli & Rosenheim (2015) for metatibia length in one species of Anagrus, and in other families of egg parasitoids, e.g., Boivin (2010) and Abram et al (2016, and references therein) discussed variation in various feature due to host, phenology, etc. Johnson et al (1987) showed that host-related antennal variation occurs in a polyphagous egg parasitoid, Telenomus alsophilae Viereck (Platygastridae, Telenominae).…”
Section: Discussionmentioning
confidence: 85%
“…However, cold-stored eggs can lose water as they age, and parasitism of such eggs may decrease with time (Kivan and Kilic, 2005;Boivin, 2010), making the use of storage conditions able to preserve the quality of host eggs important.…”
Section: Introductionmentioning
confidence: 99%
“…Insect parasitoids, that must develop using the resources available from a single host, show large phenotypic plasticity in their size mostly due to the fact that parasitoids are constrained in their immature development by the resources contained in their host (Godfray, 1994). Such intra-specific differences in size have obvious impacts on their reproductive capacity (Boivin, 2010). Smaller individuals generally have lower probability of gaining access to the other sex (Ramadan et al, 1991;Boivin and Lagacé, 1999) and have a lower fecundity and shorter life expectancy (West et al, 1996;Ellers et al, 2001;Colinet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%